Calibrated complex impedance of CHO cells and E. coli bacteria at GHz frequencies using scanning microwave microscopy. (22nd February 2016) - Tuca, Silviu-Sorin; Badino, Giorgio; Gramse, Georg; Brinciotti, Enrico; Kasper, Manuel; Oh, Yoo Jin; Zhu, Rong; Rankl, Christian; Hinterdorfer, Peter; Kienberger, Ferry
Abstract: The application of scanning microwave microscopy (SMM) to extract calibrated electrical properties of cells and bacteria in air is presented. From the S 11 images, after calibration, complex impedance and admittance images of Chinese hamster ovary cells and E . coli bacteria deposited on a silicon substrate have been obtained. The broadband capabilities of SMM have been used to characterize the bio-samples between 2 GHz and 20 GHz. The resulting calibrated cell and bacteria admittance at 19 GHz were Y cell  = 185 μ S +  j 285 μ S and Y bacteria  = 3 μ S +  j 20 μ S, respectively. A combined circuitry-3D finite element method EMPro model has been developed and used to investigate the frequency response of the complex impedance and admittance of the SMM setup. Based on a proposed parallel resistance–capacitance model, the equivalent conductance and parallel capacitance of the cells and bacteria were obtained from the SMM images. The influence of humidity and frequency on the cell conductance was experimentally studied. To compare the cell conductance with bulk water properties, we measured the imaginary part of the bulk water loss with a dielectric probe kit in the same frequency range resulting in a high level of agreement.